1998
DOI: 10.1097/00004647-199807000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Brain Networks Affected by Synchronized Sleep Visualized by Positron Emission Tomography

Abstract: Nineteen lightly sleep-deprived healthy volunteers were examined with H2(15)O and positron emission tomography (PET). Scanning was performed during wakefulness and after the subjects had fallen asleep. Sleep stage was graded retrospectively from electroencephalogram (EEG) recordings, and scans were divided into two groups: wakefulness or synchronized sleep. Global flow was quantified, revealing no difference between sleep and wakefulness. A pixel-by-pixel-blocked one-way analysis of variance (ANOVA) was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 65 publications
5
45
0
1
Order By: Relevance
“…In recent years this technique has been successfully applied to studies of natural human sleep. They not only con®rmed previous results on changes of metabolism (for a review see Maquet 1995), but also revealed brain regions in which blood ow is modulated locally by the states of sleep and waking (Maquet et al 1996(Maquet et al , 1997Braun et al 1997Braun et al , 1998Ho¯e et al 1997;Andersson et al 1998). PET with intravenously administered 15 O-labelled water (H 2 15 O-PET) requires a short acquisition time (60 s) and allows short interscan intervals (10 min).…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…In recent years this technique has been successfully applied to studies of natural human sleep. They not only con®rmed previous results on changes of metabolism (for a review see Maquet 1995), but also revealed brain regions in which blood ow is modulated locally by the states of sleep and waking (Maquet et al 1996(Maquet et al , 1997Braun et al 1997Braun et al , 1998Ho¯e et al 1997;Andersson et al 1998). PET with intravenously administered 15 O-labelled water (H 2 15 O-PET) requires a short acquisition time (60 s) and allows short interscan intervals (10 min).…”
Section: Introductionsupporting
confidence: 61%
“…The latter dierence seemed to be enhanced with the transition from Stage 2 to Stage 4, as re¯ected by the signi®cantly higher rCBF in these cortical regions. It is the ®rst time that separate scans for these two substates of NREM sleep have been analysed in the same individuals, although gradual changes from light to deep sleep have been noted (Ho¯e et al 1997;Andersson et al 1998). The similarity of the rCBF pattern for Stage 2 and Stage 4 is remarkable and is in accordance with the notion derived from quantitative EEG analysis that Stages 2, 3 and 4 have essential features in common and dier mainly in terms of sleep intensity.…”
Section: Sleep-state-related Changes Of Regional Cerebral Blood¯owmentioning
confidence: 53%
See 1 more Smart Citation
“…82 Principal components analysis of PET scan data identifi ed two brain networks associated with sleep: (1) reduced blood fl ow in frontal and parietal association cortices and hippocampus, and increased fl ow in the cerebellum; and (2) reduced blood fl ow in the thalamus and a region that, on visual inspection, overlaps with the precuneus and cuneus. 83 Lesion and structural neuroimaging studies also suggest that specifi c brain regions may be associated with insomnia. Animal studies demonstrated that lesions of the thalamus, 84 raphe nucleus, 85 or mediobasal preoptic area 86 result in insomnia.…”
Section: Structural and Functional Neuroimagingmentioning
confidence: 99%
“…In comparisons of patterns of regional CBF in sleepdeprived normal subjects during wakefulness and different sleep stages (Andersson et al 1998;Hofle et al 1997;Kajimura et al 1999;Maquet et al 1996), H 2…”
Section: Brief Review: Imaging Studies Of Sleepmentioning
confidence: 99%